2004
DOI: 10.1111/j.1440-1711.2004.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal antigens modulate the immune response associated with experimental autoimmune encephalomyelitis

Abstract: Summary Rats primed with bovine myelin (BM) in complete Freunds adjuvant, develop acute experimental autoimmune encephalomyelitis (EAE). We have previously described that intraperitoneal administration prior to the active induction of the disease of a bovine synaptosomal fraction (BSF) and BM were effective ways of suppressing EAE. We found that both treatments diminish the incidence of the disease and reduced biochemical and histological alterations of the central nervous system (CNS). To characterize this su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…These results clearly indicate that the genetic coupling of synapsin C domain to LTB constitutes a valid alternative model based probably on bystander suppression of immune response to a structurally unrelated antigen. The protective effect of LTBSC parallels the EAE suppression achieved by administration of a purified synaptosomal fraction (Degano et al, 1998, 2004).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These results clearly indicate that the genetic coupling of synapsin C domain to LTB constitutes a valid alternative model based probably on bystander suppression of immune response to a structurally unrelated antigen. The protective effect of LTBSC parallels the EAE suppression achieved by administration of a purified synaptosomal fraction (Degano et al, 1998, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…A similar inverse relationship between susceptibility to EAE and level of anti‐MBP antibodies has been previously observed (Roth and Obata, 1991; Rivero et al, 1999). Th1‐like immune response has been associated in rats with the switching of secretion of immunoglobulins toward IgG2b, and the IgG1 isotype has been associated with a Th2‐like response (Mosmann and Sad, 1996; Rivero et al, 1999; Degano et al, 2004). Anti‐MBP IgG isotypes analysis showed that only animals orally treated with LTBSC had higher titers of IgG1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation